(untitled) (Agro Productividad, 2026)
Objective: To evaluate the chemical composition, in situ dry matter degradability (ISDMD) and potential degradability of dry matter (PDDM) of maralfalfa grass. Design/Methodology/Approach: Maralfalfa grass were harvested at four maturity stages (45, 60, 90 and 120 days). The in situ dry matter degradability was determined by the nylon bag technique using two Holstein bulls provided with a ruminal cannula. Data from chemical composition, ISDMD and PDDM were analysed in a completely random design. Results: The dry matter, organic matter, ether extract, neutral detergent fiber, acid detergent fiber, crude fiber and hemicellulose values increased as the plant matured, whereas the crude protein content (13.69 to 9.73%) and total ash (17.44 o 11.20%) decreased. The in situ dry matter degradability and PDDM at 45 d, showed the highest values in relation to other maturity stages at all incubation periods (P<0.05), however, effective dry matter degradable was similar at 45 and 60 d (P <0.05). The results showed a high availability of nutrient in maralfalfa grass as indicated by the high crude protein, ISDMD, PDDM values, low neutral detergent fiber, and hemicellulose content. Study Limitations/Implications: The evaluation of the in situ dry matter degradability of maralfalfa grass allows to identify its optimal use point, in order to implement feeding strategies for based on forage or cut pastures ruminant productions systems. Findings/Conclusions: Based on changes in chemical composition, ISDMD and PDDM, 45 d of growth was considered as optimum stage of harvesting the Pennisetum sp. as a forage resource for maximum utilization of nutrients by the ruminants.